Turning points in American history - O'Donnell, Edward T.; The Great Courses (Chantilly, VA : Teaching Co., 2011)
Turning points in American history is your chance to relive the most powerful and groundbreaking moments in the fascinating story of the United States of America. These 48 lectures, delivered by master historian and dynamic professor Edward T. O'Donnell of the College of the Holy Cross, offer you a different perspective on the sweeping narrative of U. S. history. Spanning the arrival of the first English colonists to the chaos of the Civil War to the birth of the computer age and beyond, this course is a captivating and comprehensive tour of those particular moments in the story of America, after which the nation would never be the same again.
Compact discs.
In four containers (19 cm.).
Keywords: United States -- History